Effects on external pressures caused by vented explosion of methane‐air mixtures in single and connected vessels. Issue 4 (29th January 2014) - Wang, Zhirong; Pan, Moyu; Wang, Siqi; Sun, Dongliang
<x xml:space="preserve">Abstract</x> An experimental apparatus was built to study the external pressure caused by vented explosions of methane and air mixtures. In some circumstances, two peak points of external pressure induced by vented explosion appear. One of the peaks is caused by the vented flow from the vessel while the other one is due to the vented flow from the vessel or external explosion. Both the maximum external pressure and pressure rising rate increase with initial pressure, explosion venting pressure and vent diameter of the vented vessel. The maximum external pressure and pressure rising rate decrease with the volume of the vessel. The maximum pressure and the maximum pressure increase rate occur when the methane concentration is 9.5%. Compared with explosion outside one single big vessel, explosion outside the connected vessels is more severe. The external pressure caused by ignition in the center of the small vessel is higher than that in the center of the big vessel while the external pressure rising rate caused by ignition in the center of the small vessel is lower than that in the center of the big vessel. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 385–391, 2014